Attenuation of ethylene signaling increases cotton resistance to a defoliating strain of Verticillium dahliae - Tianyi Wang; Muhammad Shaban; Junhui Shi; Weiran Wang; Shiming Liu; Xinhui Nie; Yu Yu; Jie Kong; Steven J. Klosterman; Xianlong Zhang; Alifu Aierxi; Longfu Zhu (Crop Journal, 2023)
The severity of Verticillium wilt on cotton caused by defoliating strains of Verticillium dahliae has gradually increased and threatens production worldwide. Identification of the molecular components of leaf defoliation may increase cotton tolerance to V. dahliae. Ethylene, a major player in plant physiological processes, is often associated with senescence and defoliation of plants. We investigated the cotton–V. dahliae interaction with a focus on the role of ethylene in defoliation and defense against V. dahliae. Cotton plants inoculated with V. dahliae isolate V991, a defoliating strain, accumulated more ethylene and showed increased disease symptoms than those inoculated with a non-defoliating strain. In cotton with a transiently silenced ethylene synthesis gene (GhACOs) and signaling gene (GhEINs) during cotton–V. dahliae interaction, ethylene produced was derived from cotton and more ethylene increased cotton susceptibility and defoliation rate. Overexpression of AtCTR1, a negative regulator in ethylene signaling, in cotton reduced sensitivity to ethylene and increased plant resistance to V. dahliae. Collectively, the results indicated precise regulation of ethylene synthesis or signaling pathways improve cotton resistant to Verticillium wilt.